2006
DOI: 10.1016/j.molimm.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation and protein adsorption by carbon nanotubes

Abstract: As a first step to validate the use of carbon nanotubes as novel vaccine or drug delivery devices, their interaction with a part of the human immune system, complement, has been explored. Haemolytic assays were conducted to investigate the activation of the human serum complement system via the classical and alternative pathways. Western blot and sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) techniques were used to elucidate the mechanism of activation of complement via the classical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
259
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(271 citation statements)
references
References 25 publications
8
259
0
1
Order By: Relevance
“…Single walled carbon nanotubes (SWCNT) interact strongly with a large range of molecular species from dyes to polysaccharides and bio-molecules (Bandyopadhyaya et al, 2002;Chambers et al, 2003;Casey et al, 2005;Dalton et al, 2000;Hedderman et al, 2004;Keogh et al, 2004;Moulton et al, 2005;Salvador-Morales et al, 2006). Spectroscopic analysis of a commercial cell culture medium, commonly used in toxicity studies, revealed significant interaction of the constituent components with SWCNT.…”
Section: Introductionmentioning
confidence: 99%
“…Single walled carbon nanotubes (SWCNT) interact strongly with a large range of molecular species from dyes to polysaccharides and bio-molecules (Bandyopadhyaya et al, 2002;Chambers et al, 2003;Casey et al, 2005;Dalton et al, 2000;Hedderman et al, 2004;Keogh et al, 2004;Moulton et al, 2005;Salvador-Morales et al, 2006). Spectroscopic analysis of a commercial cell culture medium, commonly used in toxicity studies, revealed significant interaction of the constituent components with SWCNT.…”
Section: Introductionmentioning
confidence: 99%
“…A central methodological problem is to separate free protein from protein bound to nanoparticles, ideally employing nonperturbing methods that do not disrupt the protein-particle complex or induce additional protein binding. The preferred method to-date has been centrifugation, identifying the major serum proteins albumin, IgG and fibrinogen as being associated with a wide range of particles of seemingly disparate molecular composition (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Due to its high abundance, albumin is almost always observed on particles and may be retrieved even if it has relatively low affinity.…”
mentioning
confidence: 99%
“…Carbon nanotubes (CNTs), including single-walled carbon nanotubes (SWCNTs) and MWCNTs, have attracted much interest since Iijima [1,2] first reported in 1991. Since that time CNTs have been studied in a range of diverse applications including biological, chemical and electrical [3][4][5][6][7][8] owing to their unique mechanical, electronic and thermal properties [9,10].…”
mentioning
confidence: 99%